Frontiers in Hydropedology: Interdisciplinary Research from Soil Architecture to the Critical Zone - Li, X. (2020)
This preface for the special section provides a brief background on hydropedology as an emerging interdisciplinary science. The 10 articles included in this special section stem from presentations given at the third International Conference on Hydropedology held in August 2016 in Beijing, China, which highlighted the importance of soil architecture and preferential flow, soil moisture and hillslope hydrology, hydrologic flux and soil structure interactions at different scales, soil biophysical and biochemical complexity, and Critical Zone science.